The subgenus Choeras Mason, 1981 of genus Apanteles Foerster, 1862 (Hymenoptera, Braconidae, Microgastrinae) from China, with descriptions of eighteen new species - Song, Sheng-Nan; He, Jun-Hua; Chen, Xue-Xin (Zootaxa, 2014)
The subgenus Choeras Mason, 1981 of genus Apanteles Foerster, 1862 (Hymenoptera, Braconidae, Microgastrinae) from China is revised with 18 new species described and illustrated, and one known species redescribed. A key to the Chinese species of this subgenus is provided.